Synthesis, Pharmacological Properties, and Potential Molecular Mechanisms of Antitumor Activity of Betulin and Its Derivatives in Gastrointestinal Cancers - Marcel Madej; Joanna Gola; Elwira Chrobak (MDPI AG, 2023)
Gastrointestinal (GI) cancers are an increasingly common type of malignancy, caused by the unhealthy lifestyles of people worldwide. Limited methods of treatment have prompted the search for new compounds with antitumor activity, in which betulin (BE) is leading the way. BE as a compound is classified as a pentacyclic triterpene of the lupane type, having three highly reactive moieties in its structure. Its mechanism of action is based on the inhibition of key components of signaling pathways associated with proliferation, migration, interleukins, and others. BE also has a number of biological properties, i.e., anti-inflammatory, hepatoprotective, neuroprotective, as well as antitumor. Due to its poor bioavailability, betulin is subjected to chemical modifications, obtaining derivatives with proven enhanced pharmacological and pharmacokinetic properties as a result. The method of synthesis and substituents significantly influence the effect on cells and GI cancers. Moreover, the cytotoxic effect is highly dependent on the derivative as well as the individual cell line. The aim of this study is to review the methods of synthesis of BE and its derivatives, as well as its pharmacological properties and molecular mechanisms of action in colorectal cancer, hepatocellular carcinoma, gastric cancer, and esophageal cancer neoplasms.